The Effect Of Hyponym On Students’ Vocabulary Viewed From Motivation - Imran, Fathurrahman; Aprianoto, Aprianoto (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The problem statement of this research is hyponym effective towards students’ vocabulary at the first semester of English Department of FBMB. The aim of the research is to find out the effect of using hyponym in teaching vocabulary of first semester of English Department of FBMB. This research used quantitative research with experimental design. This research was conducted on September to November 2021. The total of students were 120 students. The researcher chose two classes as the sample of the research, namely control and experimental groups. In experimental group treated by hyponym and control group treated by vocabulary mastery and motivation. Both of the groups had been given pre-test and post-test. The sample was selected by using simple random sampling technique. This research motivation as support students’ learning especially in enhance students’ vocabulary. The result of this study, there are differences in result between post experiment and post control (82.40 >61.87). So, the use of hyponym technique can enhance students’ learning outcome while, the mean score of students’ having higher motivation is 78.284 > 62.525 is lower. It can be concluded that the students’ having higher motivation have better vocabulary than students’ having lower motivation.